مبادئ ونظريات الحوكمة من منظور الشريعة الإسلامية = Principles and theory of governance from Islamic perspective - Alnahedh, Abdulaziz; Soualhi, Younes (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2018)
يهدف البحث إلى دراسة مبادئ ونظريات الحوكمة الحديثة من منظور الشريعة الإسلامية. حيث سيركز البحث على دراسة المبادئ التسعة الأساسية للحوكمة التي حددها برنامج الأمم المتحدة الإنمائي، وهي: المشاركة، سيادة القانون، الشفافية، الاستجابة، الإجماع العام، المساواة، الفاعلية والكفاءة، المساءلة، والرؤية الاستراتيجية؛ ومدى تجذر هذه المبادئ في الشريعة الإسلامية. وبعد ذلك يناقش البحث أهم النظريات الحديثة للحوكمة، وهي: نظرية الوكالة، والمسؤولية الاجتماعية، وأخلاقيات العمل؛ حيث أنها تتداول بين الأوساط العلمية على أنها اكتشافات حديثة نسبياً، ولكن عند النظر في الشريعة الإسلامية والتراث الإسلامي نجد الكثير من الإشارات والتطبيقات لهذه النظريات والمفاهيم من خلال: نظرية الاستخلاف، وعقد الوكالة، وعقد المضاربة، والمنظومة الأخلاقية التي هي أساس النظرية الإسلامية في إصلاح الفرد والمجتمع. وفي الختام، لقد تبين أن معظم المبادئ والنظريات الحديثة المتعلقة بالحوكمة لها أسس وجذور في الشريعة الإسلامية، ولكننا كمسلمين قد تقاعسنا عن تطوير هذه الأسس بصورة تجعلها تواكب عصرنا الحالي، مما جعل الريادة في ذلك تكون للأدبيات والنظريات الغربية. ************************************************ This research aims to study the principles and theories of governance from the perspective of the Islamic Sharia. The study focuses on the nine core governance principles identified by UNDP: participation, rule of law, transparency, responsiveness, consensus orientation, equity, effectiveness and efficiency, accountability and strategic vision; and the extent to which these principles are rooted in Islam. The study then discusses the most important theories of governance: agency theory, social responsibility, and work ethic. Nevertheless, when looking at Islamic Sharia and Islamic heritage, many references and applications of these theories and concepts can be found through: The theory of alaistikhlaf, the contract of alwikala, the contract of almudaraba, and the moral system that is the basis of Islamic theory in the reform of the individual and society. In conclusion, most of the principles and theories of governance have roots in Islamic Sharia, but Muslims have failed to develop these foundations in a way that keeps them abreast of our current era, resulting in Western literature taking the lead.